China's grains policy Impacts of alternative reform options - Kimura, Shingo (OECD Food, Agriculture and Fisheries Papers, 2019)
Reforming China's grain policy could have significant implications for both domestic and international markets. China has begun to reform its price support policies for several commodities, replacing them with commodity specific area payments. The assessment of policy reform scenarios for grains, using two partial equilibrium models, show that China would maintain more than 80% of self-sufficiency in wheat and maize, and more than 95% in rice. The increase in its grain imports could increase international prices, in particular for wheat and rice. A gradual approach to reforming market price support with compensatory payments would smooth the potential impacts on domestic and world commodity markets, as well as on domestic farm income. While the reform of price support policies benefit consumers the most, more decoupled area payments could also have a greater impact on farm income without increasing the overall cost to society as well as environmental performance of agriculture. Lower costs of managing public grain stocks would equally reduce the budgetary cost of reforms